Optimization of novel reversible Bruton's tyrosine kinase inhibitors identified using Tethering-fragment-based screens. Issue 13 (1st July 2019) - Hopkins, Brian T.; Bame, Eris; Bell, Noah; Bohnert, Tonika; Bowden-Verhoek, Jon K.; Bui, Minna; Cancilla, Mark T.; Conlon, Patrick; Cullen, Patrick; Erlanson, Daniel A.; Fan, Junfa; Fuchs-Knotts, Tarra; et al.
Graphical abstract: Abstract: Since the approval of ibrutinib for the treatment of B-cell malignancies in 2012, numerous clinical trials have been reported using covalent inhibitors to target Bruton's tyrosine kinase (BTK) for oncology indications. However, a formidable challenge for the pharmaceutical industry has been the identification of reversible, selective, potent molecules for inhibition of BTK. Herein, we report application of Tethering-fragment-based screens to identify low molecular weight fragments which were further optimized to improve on-target potency and ADME properties leading to the discovery of reversible, selective, potent BTK inhibitors suitable for pre-clinical proof-of-concept studies.